$6.50(c + 18) = $6.50c + $117.00

1 answer

To solve the equation \(6.50(c + 18) = 6.50c + 117.00\), we start by expanding the left side.

\[ 6.50(c + 18) = 6.50c + 6.50 \times 18 \]

Calculating \(6.50 \times 18\):

\[ 6.50 \times 18 = 117.00 \]

Thus, we can rewrite the equation as:

\[ 6.50c + 117.00 = 6.50c + 117.00 \]

Now, we see that both sides of the equation are exactly the same. This means the equation holds for all values of \(c\). Thus, the solution is:

\[ \text{All values of } c \]